The times they are a-changin': profiling newly tenured business economics professors in Germany over the past thirty years - Mario Fernandes; Andreas Walter (Journal of Business Economics, 2023)
This study examines how the profiles of newly tenured business economics professors in Germany have changed over the past thirty years. We document how business economics professors have become more diverse over time, e.g., in terms of their gender and the internationality of their education. Furthermore, we show that the size of the professional networks of newly tenured professors increased strongly during our investigation period and that those professors who obtained tenure more recently publish with a stronger international focus than their peers who obtained tenure earlier. Most importantly, we find that the publication requirements for newly tenured business economics professors have changed over the past thirty years. Specifically, we document increased requirements for publications in highly renowned international journals. However, we also find that traditional German business economics journals (e.g., the Journal of Business Economics and the Schmalenbach Business Review ) remain highly relevant outlets for recently tenured business economics professors. Thus, by documenting and quantifying these effects, our study contributes to research on business economics professors by highlighting how the times they are a-changin' .
Keywords: A14; I23; M10; 650; Business economics; Journal articles; Publication benchmarking; Profiling; Time trends